Influence of weight resisted exercise in type 2 diabetic subjects - Cambri, Lucieli Teresa (2006)
This work had the purpose of verifying the effect of a weight resisted exercise program upon body composition and glucohemoglobin in type 2 diabetic subjects, as well as the acute effect upon capillary glucemia. Eight sedentary subjects, aged between 47 and 58 years old, composed the group. The weight resisted exercise program was constituted of 3 sessions a week. The body mass, the body mass index and the lean body mass increased. The waist/hip ratio, the 7-skinfold sum, the body fat percentage and the capillary glucemia reduced significantly. The glucohemoglobin levels did not present any significant alteration. With these results, a favorable effect of weight resisted exercise program upon body composition and capillary glucemia was observed. A possible reduction in glucohemoglobin may occur after a long-term period, considering the increased lean body mass that will, consequently, increase glucose absorption during rest as well as during physical exercise.